EFFECTIVE INNOVATIONUSING SCRUM FRAMEWORK FOR MEDIA ELEARNING AS MEDIA INTERACTIVE SYSTEM - Ruseno, Ndaru; Suprapta, Imam; Simarangkir, Manase Sahat H; Cahyadi, Cepi (The journal of contemporary issues in business and government, 2021)
Learning is an innovation from the industrial era 4.0 where learning is done online, e-learning is not a new thing. But the problem is there are still very few people who talk about how to manage an e-learning project this goes well and smoothly, the purpose of this writing is to designhow to manage e-learning projects using the agile scrum method. and the results becomes more effective. The advantage of using the found When applying this agile approach to eLearning project management.Agile management through this scrum method almost forces participants or clients to increase their participation in eLearning.